\[\begin{array}{1 1}(1)\tan^{-1}\bigg(\frac{2m}{m^{2}-1}\bigg)&(2)\tan^{-1}\bigg(\frac{2m}{1-m^{2}}\bigg)\\(3)\tan^{-1}\bigg(\frac{-2m}{1+m^{2}}\bigg)&(4)\tan^{-1}\bigg(\frac{2m}{m^{2}+1}\bigg)\end{array}\]

Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

$y=e^{-mx}$

$y=e^{mx}$

$\large \frac{dy}{dx}$$=-me^{-mx}$

$\large \frac{dy}{dx}$$=me^{mx}$

$m_2=-me^{-mx}$

$m_1=me^{mx}$

Also $e^{-mx}=e^{mx}=> \large\frac{1}{e^{mx}}$$=e^{mx}$

$e^{2mx}=1=> (e^{mx})^2=1$

$=> e^{mx}=1 => \large\frac{1}{e^{mx}}=\frac{1}{1}$

$\qquad= e^{mx}=1$

Angle between the curves

$\tan \theta= \bigg| \large\frac{m_1 -m_2}{1+m_1m_2} \bigg|$

Point of contact $x=0$

$\qquad= \large\frac{me^{mx}+me^{-mx}}{1+me^{mx}(-me^{-mx})}$

$\qquad= \large\frac{m.1+m.1}{1-m^2}$

$\qquad=\bigg| \large\frac{2m}{1-m^2}\bigg|$

$\qquad= \large\frac{2m}{m^2-1} $$ \quad m >1$

$=>\tan^{-1}\bigg(\frac{2m}{m^{2}-1}\bigg)$

Hence 1 is the correct answer

Ask Question

Take Test

x

JEE MAIN, CBSE, NEET Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...